B‐box proteins: Pivotal players in light‐mediated development in plants. Issue 9 (3rd June 2020) - Song, Zhaoqing; Bian, Yeting; Liu, Jiujie; Sun, Yuting; Xu, Dongqing
Abstract: Light signals mediate a number of physiological and developmental processes in plants, such as flowering, photomorphogenesis, and pigment accumulation. Emerging evidence has revealed that a group of B‐box proteins (BBXs) function as central players in these light‐mediated developmental processes. B‐box proteins are a class of zinc‐coordinated transcription factors or regulators that not only directly mediate the transcription of target genes but also interact with various other factors to create a complex regulatory network involved in the precise control of plant growth and development. This review summarizes and highlights the recent findings concerning the critical regulatory functions of BBXs in photoperiodic flowering, light signal transduction and light‐induced pigment accumulation and their molecular modes of action at the transcriptional and post‐translational levels in plants Abstract : This review primarily highlights the recent progress of studies on the functions of BBXs as key components of photoperiodic flowering, light signaling, and light‐induced pigment accumulation and their molecular modes of action at the transcriptional and protein levels in plants.